2023
DOI: 10.1021/acs.macromol.2c02120
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Crystallization of DNA-Functionalized Nanoparticles by Polymer Chains

Abstract: It is a challenging task to properly realize crystal superlattices with the precise organization of individual nanoparticles (NPs) for sparely DNA-functionalized NPs. In this contribution, taking advantage of flexible polymer chains for the delicate regulation of collective interactions, we overcome the challenge through a detailed investigation of the programmable self-assembly of bifunctionalized NPs by scale-accurate coarse-grained simulations. It is revealed that the rationally designed system of bifunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…We attempt to study the self-assembly of polymer-grafted nanocrystals by coarse-grained molecular dynamics (CGMD) simulation, which has been verified valid in many nanocrystal assembly systems. Although chemical details are ignored in the coarse-grained model, predicting phase behaviors and capturing the physical properties and dynamics information on an assembly process are rather reliable. In this work, we focus on three types of polymer-grafted nanocrystal systems with differently shaped cores including sphere, octahedron, and cube.…”
Section: Model and Methodsmentioning
confidence: 99%
“…We attempt to study the self-assembly of polymer-grafted nanocrystals by coarse-grained molecular dynamics (CGMD) simulation, which has been verified valid in many nanocrystal assembly systems. Although chemical details are ignored in the coarse-grained model, predicting phase behaviors and capturing the physical properties and dynamics information on an assembly process are rather reliable. In this work, we focus on three types of polymer-grafted nanocrystal systems with differently shaped cores including sphere, octahedron, and cube.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Incorporating functional groups in the core-forming block that imprint directionality during the SA process via secondary intermolecular interactions, such as hydrogen bonding, 157,[194][195][196][197][198] aromatic interactions such as π-π stacking, [199][200][201] and electrostatic interactions, 202 has been shown to widen the experimental window. Such interactions effectively overrule the packing parameter p as the main criterion defining NP morphology.…”
Section: Additional Intra-/intermolecular Interactions To Imprint Dir...mentioning
confidence: 99%
“…Subsequently, this ROPISA methodology was extended to L-leucine NCA to gain a better understanding of how the secondary structure of the polypeptide influences the NP morphology and anisotropy. 203 In addition to hydrogen bonding, aromatic interactions [199][200][201] have also been exploited: Zhu et al 199 demonstrated the synthesis of polymeric nanotubes with remarkable length, reaching up to over 11 μm, by employing an aromatic monomer with an anthracene residue for the core-forming block. Weakening the aromatic interaction by increasing the reaction temperature or adjusting the monomer composition resulted in spherical nano-objects.…”
Section: Additional Intra-/intermolecular Interactions To Imprint Dir...mentioning
confidence: 99%
“…24 Capillary filling of polymer liquid in the nanoscale also plays a critical role in many techniques such as modern lab-on-chip applications, which is instructed by the Lucas−Washburn theory where molecular weight dependence of surface tension is indispensable. 25 Furthermore, the most common technique to make polymer films or substrates with nano-pattern is based on polymer solution, even involves the exchange of solutes and polymer blends. 28−31 Therefore, it is necessary to understand the surface tension of the polymer solution for better design of more sophisticated products.…”
Section: ■ Introductionmentioning
confidence: 99%